The Effects of Chronic Stress on Migraine Relevant Phenotypes in Male Mice - Kaufmann, Dan; Brennan, K. C. (Frontiers in Cellular Neuroscience, 2018)
Migraine is a disabling neurological disorder affecting 12% of the world’s population. Stress is a major reported trigger and exacerbator of migraine. We evaluated the effects of two chronic stress paradigms on migraine relevant phenotypes in male C57Bl/6 mice. Methods: Fifty six mice were used in a 14 day social defeat stress (SDS) and twenty three mice were used in a 40 day chronic variable stress (CVS) paradigm. Anxiety measures were evaluated using the open field and elevated plus maze (EPM) tests. Migraine relevant phenotypes were evaluated using the nitroglycerin (NTG) and cortical spreading depression (CSD) models. Results: Stress sensitive SDS mice and chronically stressed CVS mice showed decreased exploration in the open field and reduced time spent in the open arms of the EPM compared to controls. Stress sensitive and resilient SDS mice had increased serum corticosterone levels, and stressed mice in the CVS paradigm had decreased weight gain compared to controls, providing combined behavioral and physiological evidence of a stress response. In the CVS paradigm but not the SDS paradigm, the stressed group showed a significant decrease in baseline mechanical withdrawal threshold compared to controls. All groups showed a significant reduction in withdrawal threshold after treatment with NTG, but the reduction was not larger in SDS or CVS than in controls. Interestingly, stress resilient SDS mice showed a rapid recovery from NTG effects that was not seen in other groups. No difference in CSD frequency or velocity was seen between stress and control mice in either stress paradigms. Conclusion: We observed distinct effects of stress on generalized pain response, migraine relevant pain, and migraine relevant excitability. CVS but not SDS was associated with a reduced mechanical withdrawal threshold, consistent with a generalized pain response to chronic stress. Neither SDS nor CVS exacerbated phenotypes considered specifically relevant to migraine - withdrawal to NTG, and susceptibility to CSD. However, the significantly reduced response of stress resilient mice to the NTG stimulus may represent a specific migraine-resistant phenotype.